Diffuse Pachymeningeal Hyperintensity and Subdural Effusion/Hematoma Detected by Fluid-Attenuated Inversion Recovery MR Imaging in Patients with Spontaneous Intracranial Hypotension - Tosaka, M.; Sato, N.; Fujimaki, H.; Tanaka, Y.; Kagoshima, K.; Takahashi, A.; Saito, N.; Yoshimoto, Y. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Fluid-attenuated inversion recovery (FLAIR) MR imaging has advantages to detect meningeal lesions. FLAIR MR imaging was used to detect pachymeningeal thickening and thin bilateral subdural effusion/hematomas in patients with spontaneous intracranial hypotension (SIH).MATERIALS AND METHODS: Eight patients were treated under clinical diagnoses of SIH. Chronologic MR imaging studies, including the FLAIR sequence, were retrospectively reviewed.RESULTS: Initial MR imaging showed diffuse pachymeningeal thickening as isointense in 6 cases, hypoisointense in 1 case, and isohyperintense in 1 case on the T1-weighted MR images, and hyperintense in all cases on both T2-weighted and FLAIR MR images. Dural (pachymeningeal) hyperintensity on FLAIR MR imaging had the highest contrast to CSF, and was observed as linear in all patients, usually located in the supratentorial convexity and also parallel to the falx, the dura of the posterior fossa convexity, and the tentorium, and improved after treatment. These characteristics of diffuse pachymeningeal hyperintensity on FLAIR MR imaging were similar to diffuse pachymeningeal enhancement (DPME) on T1-weighted imaging with gadolinium. Initial FLAIR imaging clearly showed subdural effusion/hematomas in 6 of 8 patients. The thickness of subdural effusion/hematomas sometimes increased transiently after successful treatment and resolution of clinical symptoms.CONCLUSION: Diffuse pachymeningeal hyperintensity on FLAIR MR imaging is a similar sign to DPME for the diagnosis of SIH but does not require injection of contrast medium. FLAIR is useful sequence for the detection of subdural effusion/hematomas in patients with SIH.